ΔNp63 regulates Sfrp1 expression to direct salivary gland branching morphogenesis. - Theresa Wrynn; Sangwon Min; Erich Horeth; Jason Osinski; Satrajit Sinha; Rose-Anne Romano (PLoS ONE)
Branching morphogenesis is a complex process shared by many organs including the lungs, kidney, prostate, as well as several exocrine organs including the salivary, mammary and lacrimal glands. This critical developmental program ensures the expansion of an organ's surface area thereby maximizing processes of cellular secretion or absorption. It is guided by reciprocal signaling from the epithelial and mesenchymal cells. While signaling pathways driving salivary gland branching morphogenesis have been relatively well-studied, our understanding of the underlying transcriptional regulatory mechanisms directing this program, is limited. Here, we performed in vivo and ex vivo studies of the embryonic mouse submandibular gland to determine the function of the transcription factor ΔNp63, in directing branching morphogenesis. Our studies show that loss of ΔNp63 results in alterations in the differentiation program of the ductal cells which is accompanied by a dramatic reduction in branching morphogenesis that is mediated by dysregulation of WNT signaling. We show that ΔNp63 modulates WNT signaling to promote branching morphogenesis by directly regulating Sfrp1 expression. Collectively, our findings have revealed a novel role for ΔNp63 in the regulation of this critical process and offers a better understanding of the transcriptional networks involved in branching morphogenesis.